Examining the roles of monetary and fiscal policies in Vietnam's economic growth amid global challenges: A Bayesian VAR and wavelet coherence approach - Huy, Nguyen Quoc; Dong, Nguyen Vu Hoai; Dinh, Le Quoc (International Journal of Innovative Research and Scientific Studies, 2025)
This study examines the impact of fiscal and monetary policies on Vietnam's economic growth from 1996 to 2023, particularly in the context of significant global economic challenges, including the aftermath of the COVID-19 pandemic, WTO accession, and the US-China trade war. Employing a dual-method approach with Bayesian Vector Autoregression (BVAR) and Wavelet Transform Coherence (WTC), the findings reveal that fiscal policy, measured through public consumption expenditure, strongly and positively influences economic growth, especially during key periods such as 2001–2006 (pre-WTO accession) and 2016–2021 (amid the US-China trade war and the COVID-19 pandemic). In contrast, monetary policy, represented by broad money supply, negatively affected growth, particularly between 2006–2011, when high inflation followed Vietnam's WTO accession. The study concludes that fiscal policy should serve as the cornerstone of Vietnam's economic development, with close coordination with monetary policy to ensure stability and sustainable growth, especially during periods of significant volatility. Policymakers are encouraged to emphasize counter-cyclical fiscal measures and balance inflation control with growth promotion to navigate economic challenges effectively.